The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jocn.15852
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between illness perception, fear of progression and quality of life in interstitial lung disease patients: A cross‐sectional study

Abstract: Aims and objectives:This study aimed to investigate whether fear of progression mediates the association between illness perception and quality of life among interstitial lung disease patients.Background: So far, the physiological treatment of interstitial lung disease is limited.In addition to immunosuppressants such as glucocorticoids, two anti-fibrosis drugs (pirfenidone and nintedanib) have shown moderately beneficial effects on slowing the progression of interstitial lung disease fibrosis. However, none o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Thus, economic factors have a potential impact on the psychological state of IPF patients. In addition, the fearful experience brought by disease progression may likewise lead to anxiety and depression, especially in ILDs with poor quality of life [ 18 ]. Therefore, it is necessary to explore the factors associated with combined anxiety and depression in IPF and the effects of antifibrotic therapy on the psychological status of patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, economic factors have a potential impact on the psychological state of IPF patients. In addition, the fearful experience brought by disease progression may likewise lead to anxiety and depression, especially in ILDs with poor quality of life [ 18 ]. Therefore, it is necessary to explore the factors associated with combined anxiety and depression in IPF and the effects of antifibrotic therapy on the psychological status of patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Illness perception is closely linked with disease progression and is considered malleable, encompassing both positive and negative perceptions. Previous research has indicated that positive Illness perception is associated with a higher quality of life [9,10];helping to alleviate disease suffering and regulate psychological health [11]. In contrast, negative Illness perception can reduce medication adherence [12] and cause psychological distress, affecting patients' choices in medical care [13].…”
Section: Illness Perceptionmentioning
confidence: 99%
“…The correlation between IP and social interaction has been demonstrated in many patients with chronic diseases. Prior investigations have established a compelling association between illness perception (IP) and social alienation across various patient cohorts, including those affected by interstitial lung disease [ 28 ], cancer [ 29 , 30 ], and nonepileptic seizures [ 31 ]. It is with this backdrop that we proffer a well-founded conjecture, hypothesizing an intrinsic correlation between IP and social alienation.…”
Section: Introductionmentioning
confidence: 99%